Using multiple intelligences theory in task-based language teaching - Ontaneda Rea, Mónica (Revista Universidad de Guayaquil, 2015)
It is important to know that language learning is a process that involves perception, memory, thinking, imagination and many intellectual factors that let us gain knowledge in different ways. Therefore, the theory of multiple intelligences focuses on a learning process as an important key to work with a variety of students’ abilities. Besides, the concept of MI theory lets teachers explore that intelligences in teaching a language is changing the conventional methods into task-based approach used for real situations, helping teachers to systematically and comprehensively develop a variety of intelligences that promote English teaching quality and get good results with students.
Keywords: Multiple Intelligences; task-based pedagogy; English; language